Pertanggungjawaban Hukum Terhadap Pelaku usaha Dalam Konsep Business To Customer Melalui Transaksi Elektronik - Batubara, Efraim; Hasan, Umar; Windarto, Windarto (Zaaken: Journal of Civil and Business Law, 2023)
This research aims to find out how the responsibility of business actors towards consumers is regulated in the event of a dispute and to find out and analyze the conflicts contained in the regulations regarding dispute resolution between consumers and business actors at the Consumer Dispute Resolution Agency. The method used in this thesis is normative juridical research with a conceptual approach, laws and interpretation according to language using legal materials in the form of Law Number 8 of 1999 concerning Consumer Protection. The results of this research are: 1) Whereas from a juridical perspective, the legal responsibility of business actors towards consumers in the event of a dispute has indeed been regulated in statutory regulations, so that this can be used as a basis if you want to resolve a dispute. 2) That there is a conflict that occurs in the regulations regarding dispute resolution between consumers and business actors. In Article 54 of the Law, it is stated that the decision is final and binding from the Consumer Dispute Resolution Agency, which actually conflicts with the provisions in Article 56 which states that parties can make objections to the decision. The objection in question is to make an appeal to the District Court and cassation to the Supreme Court. So if this is maintained it will cause consumer protection efforts to be less than optimal.